Media Ethnography in Diasporic Communities - Putut Widjanarko (Humaniora, 2020)
Media and communication technology plays a crucial role in diasporic communities by helping members to maintain complex connections with their places of origin, and at the same time to live their life in the diaspora. The social interactions, belief systems, identity struggles, and the daily life of diasporic communities are indeed reflected in their media consumption and production. A researcher can apply media ethnography to uncover some of the deeper meanings of diasporic experiences. However, a researcher should not take media ethnographic methods lightly since a variety of issues must be addressed to justify its use as a legitimate approach. This article examines various forms of media ethnographic fieldwork (multi-sited ethnography), issues related to researching one’s own community (native ethnography), and the debates surrounding duration of immersion in ethnography research within the context of diasporic communities. Careful consideration of such issues is also necessary to establish the “ethnographic authority” of the researcher.